Association Between Transient Hypothyroxinaemia of Prematurity and Adult Autism Spectrum Disorder in a Low‐Birthweight Cohort: An Exploratory Study. Issue 2 (4th February 2013) - Korzeniewski, Steven J.; Pinto‐Martin, Jennifer A.; Whitaker, Agnes H.; Feldman, Judith F.; Lorenz, John M.; Levy, Susan E.; Movsas, Tammy Z.; Pappas, Athina; Paneth, Nigel
Abstract: Background: Transient hypothyroxinaemia of prematurity (THOP) is associated with increased risk of cerebral palsy and lower IQ in low‐birthweight infants. This study explores whether THOP is also associated with increased risk of autism spectrum disorders (ASD). Methods: This secondary analysis uses data from a birth cohort of newborns weighing 500 –2000 g ( n = 1105) who were followed to age 21 years, when they were assessed for ASD in the second of a two‐stage process. Of the 187 assessed at age 21, 14 had ASD. Neonatal thyroxine results were available for 12/14 and 165/173 participants diagnosed with and without ASD, respectively. THOP was defined as thyroxine z ‐score <−2.6. Unadjusted relative risks (RR) and confidence intervals (CI) were calculated. Results: The mean neonatal thyroxine z ‐score in young adults diagnosed with ASD was 0.5 SD lower [95% CI −0.16, 1.06] than in those without ASD. Participants with THOP were at 2.5‐fold greater risk of ASD (RR 2.5 [95% CI 0.7, 8.4]). While neither of these differences was statistically significant, in a secondary subgroup analysis of those whose mothers did not have hypertension during pregnancy, THOP significantly increased the RR for ASD (5.0 [95% CI 1.2, 20.5]). Conclusion: While the primary relation between THOP and ASD found here is not statistically significant, the magnitude of association and significant relationship observed in the subgroup whose mothers did not have hypertension during pregnancy suggest that it is worthy of further investigation.